Kittens gonadectomy: anesthesic technique - Mastrocinque, Sandra; Imagawa, Vivianne Higuchi; Almeida, Tatiana Ferrante de; Tatarunas, Angelica Cecília; Matera, Julia Maria; Fantoni, Denise Tabacchi (Brazilian Journal of Veterinary Research and Animal Science, 2006)
The aim of this study was to evaluate an anesthetic protocol in female kittens to perform gonadectomy. Forty female kittens with ages varying from 2 to 4 months old, mixed breed were used. They were premedicated with acepromazina plus meperidina and the induction and maintenance of anesthesia were performed with tiletamine-zolazepam. Variables measured were: cardiac and respiratory rates, oxyhemoglobin saturation, temperature, surgical relaxation, surgical and recovery times, recovery and undesirable effects. There was a reduction of respiratory rate after induction of anesthesia and cardiac rate remained stable during anesthesia period. Two animals needed oxygen therapy by facial mask and animals' recovery was smooth. The surgical relax was obtained in all animals and there were no other side effects. Based on these results it can be concluded that the anesthetic procedure was safe and effective to perform gonadectomy in female kittens.